2013
DOI: 10.1292/jvms.13-0310
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Demonstration of the Absorption and Transportation of Minute Chylomicrons by Subepithelial Blood Capillaries in Rat Jejunal Villi

Abstract: Chylomicrons from villous columnar epithelial cells are generally known to be transported only by central lymph vessels (CLV), whereas antigenic particulates derived from the intestinal lumen can also be transported by subepithelial blood capillaries (sBCs) in rat intestinal villi. The possibility of chylomicron absorption by sBCs was histoplanimetrically studied in the rat jejunum under a transmission electron microscope. The chylomicrons more abundantly presented in villous venules than in arterioles. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Mature CM particles exit the enterocytes at the basolateral membrane by exocytosis into intercellular spaces and the lamina propria, before entering the lacteals, larger mesenteric lymphatics, and the thoracic duct, and ultimately enter the blood circulation. The presence of CM particles along this secretory pathway has been identified in the intercellular spaces, the lamina propria, and lymphatic vessels (Robertson et al, 2003;Takahara et al, 2013;Xiao et al, 2018b). These extracellular CMs, which appear to be retained for many hours after food ingestion (Xiao et al, 2018b), may also be a source of mobilized intestinal lipid and CMs in the post-absorptive period.…”
Section: Locations Of Tg Storage In the Gutmentioning
confidence: 99%
See 2 more Smart Citations
“…Mature CM particles exit the enterocytes at the basolateral membrane by exocytosis into intercellular spaces and the lamina propria, before entering the lacteals, larger mesenteric lymphatics, and the thoracic duct, and ultimately enter the blood circulation. The presence of CM particles along this secretory pathway has been identified in the intercellular spaces, the lamina propria, and lymphatic vessels (Robertson et al, 2003;Takahara et al, 2013;Xiao et al, 2018b). These extracellular CMs, which appear to be retained for many hours after food ingestion (Xiao et al, 2018b), may also be a source of mobilized intestinal lipid and CMs in the post-absorptive period.…”
Section: Locations Of Tg Storage In the Gutmentioning
confidence: 99%
“…CMs are believed to move through the lamina propria via diffusion, largely influenced by convective movement of fluids (Tso and Balint, 1986). Subsequently, CMs enter the lymphatic system from the lamina propria via the lacteals (Takahara et al, 2013). Although a transcellular pathway has been described, the majority of CMs enter lacteals by a paracellular pathway via large, porous, intercellular junctions at the tip of the lacteal.…”
Section: Entry Into the Lymphaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until quite recently, chylomicrons discharged into the lamina propria from the villous columnar epithelial cells were thought to be transported only by the central lymph vessels (CLV) and never by blood capillaries in the intestinal villi [ 10 , 11 , 23 ]. However, a previous ultrastructural and histoplanimetrical study demonstrated that a portion of the minute chylomicrons less than 75 nm in diameter are transported by not only CLV but also subepithelial blood capillaries (sBC) and that minute chylomicrons encapsulated by cell membranes are transported into the lumina of the sBC through endothelial cells in the rat jejunum [ 41 ]. From these findings, the transportation of minute chylomicrons into the lumina of sBC is assumed to be performed by receptor-mediated transcytosis in the endothelial cells of sBC.…”
mentioning
confidence: 99%
“…Therefore, the minute chylomicrons in the broad sense— i.e. , less than 75 nm in diameter [ 41 ]—are assumed to be recognized and bound by VLDL receptor or LDL receptor on the endothelial cells of sBC in the rat small intestine. The aim of the present study was to demonstrate the contribution of VLDL receptor or LDL receptor to the transportation of minute chylomicrons into the lumina of sBC in the rat jejunum.…”
mentioning
confidence: 99%